(untitled) (FAVE Sección Ciencias Agrarias, 2024)
Neltuma alba, known as “algarrobo blanco” is an important native species in the Chaco ecoregion, particularly in Argentina, due to its biological, productive, and cultural value. Overexploitation of its timber is causing a loss in the species’ genetic diversity. Vegetative propagation in vitro is emerging as a biotechnological tool for conserving forest genetic resources. This study aimed to assess the effects of different types and concentrations of auxins on the in vitro rooting response of N. alba. The results indicate that explants have the ability to develop adventitious roots with or without the presence of plant growth regulators, though higher concentrations of auxins induce a better rooting response. Subculturing explants in an auxin-free medium after 7 days of exposure to 4 mg/l of IBA has shown to reduce callus formation and minimize root malformations. This working methodology allows achieving a 75% survival rate of ex vitro plants.